A Scenario of Implementation Building Information Modelling (BIM) Technology in the Interior Design Industry - Bakar Abd Hamid, Abu; Rashid Embi, Mohd; Zafrullah Mohd Taib, Mohd; Haqqi Nazali Abdul Razak, Ahmad (International Journal of Engineering and Technology, 2018)
While Building Information Modelling are established in construction industry especially in architectural, engineering and construction (AEC), interior design is still struggles and freshly in this technology. BIM is a new paradigm in a construction industry to enhance the construction progress and documentation more efficient and fast. The main research is to emphasize the scenario of implementation building information modelling for interior design industry in Malaysia context. The research explores how crucial the adoption BIM for interior design firms in industry. This study is embark on collecting data through a pilot survey which is several interior design firms registered with Board of Malaysia Architect (LAM) was chosen. The research outcomes are to find out the problems why interior design industry in Malaysia is unimplements BIM technology in interior design industry. This study also will be figure up the solution on adoption of BIM in interior design industry.